Bridging the protein gap with single-cell protein use in aquafeeds - Buttle, Louise; Noorman, Henk; Roa Engel, Carol; Santigosa, Ester (Frontiers in Marine Science, 2024)
Blue foods from aquaculture are essential in bridging the protein gap to feed the human population in the future. However, for aquaculture production to be sustainable, production must be within planetary boundaries, and sourcing of sustainable raw materials is a key driver in sustainable production. This article explores the role of single-cell proteins (SCPs) derived from microorganisms in aquafeeds. Three main aspects are discussed: sustainability, scalability of fermentation technology, and fish performance. In addition, and through a comprehensive proof-of-concept trial with rainbow trout (Oncorhynchus mykiss), this article demonstrates SCP’s efficacy in replacing traditional feed ingredients without compromising fish growth and health. The trial’s findings demonstrate a high protein digestibility and a balanced amino acid profile, as well as health benefits measured through oxidative burst response. To date, commercial adoption of SCP has been hindered by high production costs and the need for substantial investments to scale fermentation technologies. However, the sustainability landscape is changing as large industry players openly commit to sustainability targets and realize that longer-term and investment thinking into the future is needed. In conclusion, SCP emerges as a promising avenue for sustainable aquafeeds, offering a solution to the protein supply challenge within planetary boundaries. In addition, in terms of environmental benefit, SCP shows clear advantages regarding land use, carbon emissions, biodiversity impact, and water consumption. Ultimately, the successful integration of SCP into aquafeeds could significantly contribute to the industry’s sustainability goals and play an essential role in securing the future supply of raw material proteins.